2022
DOI: 10.3390/polym14245441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of In Vitro Degradation on the Properties of Samples Produced by Additive Production from PLA/PHB-Based Material and Ceramics

Abstract: The present study deals with preparing a polymer-based material with incorporated ceramics and monitoring changes in properties after in vitro natural degradation. The developed material is a mixture of polymers of polylactic acid and polyhydroxybutyrate in a ratio of 85:15. Ceramic was incorporated into the prepared material, namely 10% hydroxyapatite and 10% tricalcium phosphate of the total volume. The material was processed into a filament form, and types of solid and porous samples were prepared using add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Balogová et al described a biocompatible material consisting of PLA polymers with the addition of ceramics suitable for 3D cultivation of chondrocytes in which long-term biodegradation was monitored in a simulated physiological environment. The results of the study showed that the biodegradation of the material was gradual, and the material appeared to be stable in the organism's environment [151]. Trebu ňová et al tested the composite material PLA/PHB for cultivation and cytotoxicity while evaluating the most optimal ratio of individual components for the mentioned parameters.…”
Section: Biocompatible Synthetic Scaffoldmentioning
confidence: 99%
“…Balogová et al described a biocompatible material consisting of PLA polymers with the addition of ceramics suitable for 3D cultivation of chondrocytes in which long-term biodegradation was monitored in a simulated physiological environment. The results of the study showed that the biodegradation of the material was gradual, and the material appeared to be stable in the organism's environment [151]. Trebu ňová et al tested the composite material PLA/PHB for cultivation and cytotoxicity while evaluating the most optimal ratio of individual components for the mentioned parameters.…”
Section: Biocompatible Synthetic Scaffoldmentioning
confidence: 99%
“…Hydroxyapatite (HA) is the major mineral component of natural bone, and it is one of the most investigated and used inorganic biomaterials for bone regeneration. HA ceramics are biocompatible, with a high osteogenic potential and low biodegradability [6,7], but also possess poor mechanical properties, including brittleness, low fatigue, and mechanical stress resistance, restricting their clinical applications [8]. In the last decades, nanostructured hydroxyapatite (nano-HA) has been proposed as an alternative, since its morphology increases the contact area with the host, resulting in a higher biodegradability and higher biological activity, able to accelerate the bone regeneration process [9,10].…”
Section: Introductionmentioning
confidence: 99%